Control of Escherichia coli O157:H7 in large-diameter, Lebanon-style bologna - K.J. Karr; Curtis L. Kastner; James L. Marsden; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 1998)
Lebanon bologna raw batter was mixed with a five-strain mixture of Escherichia coli O157:H7 to achieve average inoculum levels of 7.79, 7.77, and 7.92 log CFU/g as deter mined on MSA, 202, and PRSA media, respectively. Treatment 1 consisted of a fermentation cycle of 8 hrs at an internal temperature (I.T.) of 80EF then 24 hrs at 100EF I.T., followed by 24 hrs at 110EF I.T. Treatments 2, 3, and 4 included additional heating at 115EF I.T. for 1, 2, and 5 hrs, respectively. All heat treatments resulted in product that was negative (<1.9 log CFU/g detection limit) on all culture media and negative after enrichment on mEC selective medium. This study validates that a five-log reduction of E. coli O157:H7 can be achieved using the described protocol, thus meeting USDA/FSIS requirements.
Keywords: Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 804; Cattlemen' s Day; 1998; Beef; E. coli O157:H7; Food safety; Fermented beef; Sausage